PENERAPAN SISTEM REFRIGERASI PADA ALAT PEMBUAT ASAP CAIR UNTUK PENGOPTIMALAN HASIL PRODUKSI - Sumarna, Herlin; ., Haryanto; Hidayati, Baiti; Homzah, Ozkar F (AUSTENIT, 2020)
Recently, liquid smoke is widely used for various needs, both for food purposes and for freezing rubber latex. Liquid smoke began to grow due to the large demand, also using biomass / waste as a base material. Immediate production results are needed by the condensation process. The application of the refrigeration system guides the temperature of the air which is used as a cooling medium in the condensation process during the process of making liquid smoke. This study uses coconut shell as raw material for pyrolysis, and there are 4 temperature variations that are applied in the liquid smoke production process. First without a refrigeration system, the application of a refrigeration system with temperature variations of 22 ° C, 18 ° C and the last one is 15 ° C. The data is taken every 30 minutes for 6 hours. Based on the research results, it was found that the maximum production results using the refrigeration system at an air temperature of 15 ° C, resulted in 375 ml of liquid smoke. Keywords: Liquid Smoke, Refrigeration, Pyrolysis, Coconut Shell